2020
DOI: 10.1021/acsami.0c07612
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Aggregation-Induced Delayed Fluorescence Emitters Featuring the Asymmetric D–A Structure with a Novel Diarylketone Acceptor Toward Efficient OLEDs with Negligible Efficiency Roll-Off

Abstract: Multifunctional luminescent materials with aggregation-induced delayed fluorescence (AIDF) are capable of suppressing concentration-caused emission quenching and exciton annihilation when used as organic light-emitting diode (OLED) emitters. In this contribution, three stimuli-responsive AIDF luminogens, pipd-BZ-PXZ, pipd-BZ-PTZ, and pipd-BZ-DMAC, featuring a D–A asymmetric framework based on a fused N-heterocycle diarylketone acceptor (imid-azo­[1,2-a]­pyridin-2-yl­(phenyl)­methanone pipd) are designed and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…10–13 Additionally, it is an effective way to investigate crystal-packing and structure–property relationships. 14,15 Z. Chi reported a chromophore with phenoxazine and phenothiazine as donors (D) and diphenyl sulfone as an acceptor (A), realizing full-color emission, peaking in the range of 469 nm to 583 nm, from ten individual single crystals, ranging from normal fluorescence to room-temperature phosphorescence. 16…”
Section: Introductionmentioning
confidence: 99%
“…10–13 Additionally, it is an effective way to investigate crystal-packing and structure–property relationships. 14,15 Z. Chi reported a chromophore with phenoxazine and phenothiazine as donors (D) and diphenyl sulfone as an acceptor (A), realizing full-color emission, peaking in the range of 469 nm to 583 nm, from ten individual single crystals, ranging from normal fluorescence to room-temperature phosphorescence. 16…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the EL spectra resembled to the FL spectra of the two emitters revealed that the EL really stemmed from the emitting layers. [ 57 ]…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Yang et al 127 reported two D–A type aggregation‐induced delayed fluorescence (AIDF) emitters, pipd ‐BZ‐PXZ, pipd ‐BZ‐PTZ (Figure 10A), where a fused N‐heterocycle (imid‐azo[1,2‐a]pyridin‐2‐yl(phenyl), pipd ) and diarylketone acceptor served as acceptor, and phenoxazine (PXZ), phenothiazine (PTZ) group functioned as donors respectively. Owing to the embedded two nitrogen atoms, the pipd exhibited very strong electron‐withdraw ability, which favors the ICT effect and red‐shifted emission.…”
Section: Rational Molecular Design Of Red and Nir Aiegensmentioning
confidence: 99%
“…(A) Chemical structure of pipd ‐BZ‐PXZ and pipd ‐BZ‐PTZ; (B) PL spectra of pipd ‐BZ‐PXZ in THF/water mixtures with various f w ; (C) plots of I / I 0 versus f w (red) and emission wavelength change (blue) upon increasing the water content, I 0 stands for the PL intensity in THF, and the inset presents PL images under f w of 0%, 50%, and 99%, respectively; (D) chemical structure of BenCN‐PXZ and BDCN‐PXZ; (E) EL spectra measured at 10 mA cm −2 from the doped OLED based on emitters of BenCN‐PXZ (5 wt% in CBP) and BDCN‐PXZ (20 wt% in CBP); (F) EQE versus luminance plots of the two OLED devices. Reproduced (Adapted) with permission 127,128 . Copyright 2020, American Chemical Society.…”
Section: Rational Molecular Design Of Red and Nir Aiegensmentioning
confidence: 99%